Modulation of the pro-inflammatory molecules E-selectin and TNF-α gene transcription in Eimeria ninakohlyakimovae-infected primary caprine host endothelial cells. Issue 5 (October 2015) - Pérez, D.; Ruiz, A.; Muñoz, M.C.; Molina, J.M.; Hermosilla, C.; López, A.M.; Matos, L.; Ortega, L.; Martín, S.; Taubert, A.
Abstract Eimeria ninakohlyakimovae is an important coccidian parasite of goats which causes severe hemorrhagic typhlocolitis in young animals, thereby leading to high economic losses in goat industry worldwide. The first merogony of E. ninakohlyakimovae occurs within host endothelial cells (ECs) of the lacteal capillaries of the villi of the distal ileum resulting in the formation of macromeronts (up to 170 μm) within 10–12 days post-infection (p.i.) and releasing > 120, 000 merozoites I. The E. ninakohlyakimovae-macromeront formation within highly immunoreactive host endothelial cells (ECs) should rely on several regulatory processes to fulfill this massive replication. Here host EC–parasite interactions were investigated to determine the extent of modulation carried out by E. ninakohlyakimovae in primary caprine umbilical vein endothelial cells (CUVEC) during the first merogony. Gene transcription of the adhesion molecule E-selectin and the cytokine TNF-α were significantly enhanced in the first hours and days p.i. in E. ninakohlyakimovae-infected CUVEC. The activation of CUVEC was also demonstrated by enhanced chemokine CCL2 and cytokine GM-CSF gene transcription, whereas no differences of the eNOS gene transcription were observed in E. ninakohlyakimovae-infected CUVEC when compared to un-infected controls. The data presented here suggest that infection of caprine host ECs by E. ninakohlyakimovae results in EC activation associated with enhanced gene transcription encoding for pro-inflammatory as well as immunomodulatory molecules, which might be important for the defense against this intracellular parasite.